Адаптаційні аспекти застосування економічної експертизи в контурах німецької моделі контролінгу підприємства - Перевозова, І. В. (Видавництво Львівської політехніки, 2014)
Визначено адаптаційні аспекти застосування економічної експертизи в контурах моделі контролінгу А. Дайле, наведено взаємоузгодженість основних завдань контролінгу та економічної експертизи. Удосконалене графічне зображення піраміди тотального контролінгу в мультифункціональному організаційному утворено в контурах моделі А. Дайле. In this article the adaptive aspects of the economic expertise in the circuits controlling model of A. Dayle. In this approach, contours availability subsystem economic expertise be implemented in two groups of tools: tools of planning and regulation of subdivisions (a function of business process management) and management tools and incentives for workers (people management function). Thus, for each set of business processes, goals of controlling is actually derived from the objectives of the enterprise and are a direct reflection of the prevailing to solve problems. It is proved that the approach A. Dayle is to formulate target picture company that identifies and specifies its goals. The formation of this pattern is its quality description of the problem facing the company. Her actual presence serves stimulant motivate employees to achieve a goal. Emphasized that it was their decision, but primarily on the accuracy of the formulation, the achievement now. The challenge to the decision, concerning the economic and expert research to fully correlate with the main tasks of controlling, so interconsistency article describes the main tasks of controlling and economic expertise. Author`s representation of the pyramid of the total controlling multi-organizational created in the contours of A. Dayle’s model reflects ensuring the proper task of controlling, namely building an effective system for enterprise adoption, implementation, monitoring and analysis of management decisions.
Adaptation aspects of economic expertise in the circuit controlling the german model enterprise
Keywords: підприємство; контролінг; інструменти; моделі; економічна експертиза; адаптація; моделювання; бізнес-процеси; економічний зміст; enterprise; controlling; tools; models; economic assessment; adaptation; modeling business processes; the economic content